Strategi Integrasi Manajemen Keuangan Dan Pemasaran Berbasis Kewirausahaan Pesantren Dalam Meningkatkan Kemandirian Ekonomi Santri Di Pondok Pesantren Al Muqriyah - Aufa Bintang Hafian; Dominggos Boro Meu; Kayla Refalina Azzahra (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This community service activity aims to improve students’ understanding of financial management and marketing strategies based on pesantren entrepreneurship to support economic independence. Pesantren has great potential in developing independent businesses; however, students still face limitations in financial recording, capital management, and product promotion. The activity was conducted at Al Muqriyah Islamic Boarding School on Thursday, November 27, 2025 using counseling, discussion, and simple simulations. The materials covered basic financial management, marketing strategies, and entrepreneurial mindset development. The results indicate an improvement in students’ awareness of orderly financial management, effective marketing practices, and increased independence in managing business activities. This program is expected to contribute to the sustainable economic independence of students.